Job Burnout and Performance as a Determinant of Organisational Loyalty of Records Professionals - Durodolu, Oluwole Olumide; Marutha, Ngoako Solomon (Mousaion: South African Journal of Information Studies, 2024)
This article reports on a study that investigated the effect of job burnout and job performance as a determinant of organisational loyalty of records managers in South-Western Nigeria. The research sample comprised archivists and records managers at the University of Ibadan, College of Medicine, and the Federal University of Agriculture, Abeokuta, Ogun State (FUNAAB) that warehouse the largest collection of government records in Nigeria. The research methodology was informed by the positivist research paradigm and used a questionnaire. The data analysis and interpretation of results were in descriptive form, using tables of frequencies and percentages. PPMC and regression analyses were presented. The results and discussions covered the demographic characteristics of respondents, answers to research questions, and answers to research hypotheses. The findings revealed that the marital status of the majority of respondents was single, and the dominant gender was female. The level of job burnout was moderate, illustrating that occupational pressure is temperate. The records professionals seemed satisfied with prospects of contributing to the organisation’s development, training opportunities, communication and teamwork, accounting for their commitment to organisational goals and their loyalty to the establishment. The results also reveal that career advancement, recognition and employment benefits are the major factors determining the loyalty of records professionals. The positive connection between the variables implies that improvement in job burnout prevention would lead to an increase in loyalty to their organisation. By recognising the impact of job burnout and promoting high performance, organisations can enhance the organisational loyalty of archivists and records managers, leading to improved retention, productivity, and overall success.